Association Between Online Gaming, Dietary Patterns, and Nutritional Status Among Medical Students Class Of 2024 - Adi, Paul Immanuel; Rumiati, Flora; Rickie, Rickie; Heriyanto, Heriyanto (Jurnal MedScientiae, 2026)
The rapid expansion of online gaming among university students may influence dietary patterns, nutritional status, sleep patterns, and physical activity, which are critical for long-term health. This study was motivated by concerns that online game addiction could be associated with malnutrition and sedentary behavior among medical students. The aim of this research is  to determine the association between online game addiction and dietary patterns, nutritional status, sleep patterns, and physical activity among medical students of Universitas Kristen Krida Wacana class of 2024. An analytical cross-sectional study was conducted involving 80 medical students selected using nonprobability purposive sampling based on predefined inclusion criteria. Data were analyzed using univariate and bivariate methods with Chi-Square or Fisher Exact tests at a significance level of p<0.05. Online game addiction was not associated with meal frequency p 0.746, food variety p 0.896, or sleep patterns p=0.706. A borderline association was found with nutritional status p=0.051, and a significant association was observed with physical activity p=0.036. Online game addiction among these medical students appeared to be more closely related to nutritional status and physical activity than to dietary and sleep patterns.